SKRINING DAN EDUKASI PENYAKIT TIDAK MENULAR DUKUH MARANGAN, DESA JIMBUNG, KECAMATAN KALIKOTES, KABUPATEN KLATEN - Allya Salma Arifianty; Reinascita Nurcartenzia; Gwenda Ariviaquina Ahmad; Dewanto Dika Pratama; Khoirunisa Puspaning Putri; Alya Salsabila Amirah; Febya Arka Walid Oktaviano; Elvaretta Angie Claresta; Salsabila Ivana; Cindy Az-Zahra Ivano Chory; Romdhoni Yoga Nugroho; Nurul Mukaromah; Cut Salsabila Alya Zahra; Haris Setyawan (J-ABDI: Jurnal Pengabdian kepada Masyarakat, 2025)
Non-communicable diseases (NCDs) are a major health problem in the world. Many of these NCDs appear without showing certain clinical signs, so people do not realize the danger of the disease. In Klaten Regency, the prevalence of Diabetes Mellitus and Hypertension based on the 2020 Klaten Regency Health Profile stated that the prevalence of Diabetes Mellitus was 37,485 people and Hypertension was 102,089 cases. The increasing prevalence of Diabetes Mellitus and Hypertension will indirectly increase the morbidity and mortality rates due to its complications, so it is estimated that it will increase the burden on society and government. Thus, to realize this, it is necessary to carry out screening, education, and evaluation activities for NCDs for early detection to identify risk factors and early signs of disease, prevention, better management and appropriate counseling. The method used in the article uses a community-based approach, NCDs screening and education activities in Dukuh Marangan are carried out in each RW, namely RW 06, RW 07, and RW 08 with the target age of 15-59 years. This screening was continued at existing community activities, such as PKK meetings, Posyandu for the Elderly, and Youth Posyandu, so that the total number of respondents was 125 people. The results of the analysis of the pre-test and post-test scores of respondents in NCDs screening and education activities showed a significant increase in knowledge. The average pre-test score increased from 5.40 to 7.08 in the post-test. The Wilcoxon Matched-Pairs test showed a significance value (p-value) of 0.000 (<0.05), indicating a significant increase in knowledge among respondents after participating in the NCDs evaluation activities. These results show that education and screening activities are effective in improving community understanding of NCDs and their prevention efforts, and make a positive contribution to community health, especially in Dukuh Marangan